FAKTOR-FAKTOR YANG MEMPENGARUHI ANEMIA PADA IBU HAMIL DI PUSKESMAS PADEDIWATU KABUPATEN SUMBA BARAT - Maria Kondi (STIKes CHMK, 2017)
ABSTRACT Pregnancy is the beginning of a new life period of growth. The period of pregnancy is a very important period for the formation of quality human resources in the future, because the growth of children will be determined by the conditions at the time the fetus in the womb. Anemia is a health problem especially for women of reproductive age and pregnant women. The most common causes of anemia in pregnancy are iron deficiency, folic acid, and acute bleeding and can occur due to interactions between the two.The purpose of this study was to find out the description of factors That affecting anemia in pregnant women at Padediwatu Sumba Barat Public Health Center.The method used in this research is descriptive with cross sectional study design. Total respondent 63 with sampling technique using total sampling with instrument used in this research is questionnaire.Respondents with age category 20-30 years with high school education level, diet always, adhering to consume tablet Fe, socioeconomic status of minimum and maximum wage, with distance of pregnancy> 2 years and most respondents had mild anemia.For respondents who have anemia still maintain the condition so it does not arrive at severe anemia. Keywords: Anemia, Pregnant Woman